Exercise From the Perspective of Iranian Traditional Medicine - Narges Motahari Tabari; Seyde Sedighe Yousefi; Ghazaleh Heydarirad; Maryam Kardan Soraki; Payam Habibipour (SAGE Publishing, 2017)
Exercise, in Iranian traditional medicine, is 1 of the 6 principles recommended for maintaining good health. There are some considerations that must be taken into account before, during, and after exercise. Exercise has different terms in different individuals, seasons, and ages. According to these principles, the interval between exercise and eating food is very important. Exercise after eating is inappropriate, and it is recommended that the best time for exercise is after food has been completely digested and before the next meal. According to the opinion of traditional medicine philosophers, exercise should be done after the complete digestion of food. Exercise may be more effective if it is done according to traditional medicine view at appropriate times and conditions with sufficient intensity and duration.